2019
DOI: 10.1155/2019/3875147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CERS2 Gene as a Potential Biomarker for Bladder Cancer

Abstract: The ceramide synthase 2 (CERS2) gene has been linked to tumour recurrence and invasion in many different types of cancers including bladder cancer. In this study, the expression levels of CERS2 in bladder cancer cell lines were analysed using qRT-PCR and the protein expression in clinical bladder cancer histopathological specimens were examined via immunohistochemistry. The potential utility of CERS2 as a predictive biomarker of response to oncolytic virotherapy was assessed by correlating the CERS2 mRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…CerS1 specifically synthesizes C18 ceramide, and while it is highly expressed in the skeletal muscles, it is nearly undetectable in other tissues ( 24 ). CerS2 is mostly expressed in the kidneys and liver, and synthesizes C22-24 ceramides ( 25 ). Ceramides with varying acyl chain lengths may trigger diverse cell responses; hence, different CerS isoforms may create different ceramide species ( 17 ).…”
Section: Biosynthesis and Degradation Of Ceramidesmentioning
confidence: 99%
“…CerS1 specifically synthesizes C18 ceramide, and while it is highly expressed in the skeletal muscles, it is nearly undetectable in other tissues ( 24 ). CerS2 is mostly expressed in the kidneys and liver, and synthesizes C22-24 ceramides ( 25 ). Ceramides with varying acyl chain lengths may trigger diverse cell responses; hence, different CerS isoforms may create different ceramide species ( 17 ).…”
Section: Biosynthesis and Degradation Of Ceramidesmentioning
confidence: 99%
“…The potential utility of CERS2 as a predictive biomarker of response to oncolytic virotherapy has also been investigated [ 89 ]. Unfortunately, the potential of CERS2 as a predictive biomarker was found to be limited but may have the potential as a therapeutic target for bladder cancer, since the siRNA-mediated downregulation of CERS2 expression resulted in reduced bladder cancer cell migratory potential [ 90 ].…”
Section: Homeobox Genes In Bladder Cancermentioning
confidence: 99%
“…Urothelial cancer is the most common type of BLCA and is classified into muscle‐invasive bladder cancer (MIBC; accounting for 25–30% of the cases) and non‐muscle‐invasive bladder cancer (NMIBC; accounting for 70–75% of the cases). Non‐invasive BLCA presents with limited and superficial lesions, whereas invasive BLCA is characterized by invasion of the muscle layer and is treated with total bladder resection and urinary diversion 4,5 . Epidemiological studies have reported that most NMIBCs are low‐grade, while most MIBCs are high‐grade 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive BLCA presents with limited and superficial lesions, whereas invasive BLCA is characterized by invasion of the muscle layer and is treated with total bladder resection and urinary diversion. 4,5 Epidemiological studies have reported that most NMIBCs are low-grade, while most MIBCs are high-grade. 6 The treatment and prognosis of BLCA depend on the degree of local lesion invasion and type: NMIBCs (<T2 stage) are treated with transurethral resection of the bladder tumor, whereas MIBCs (≥T2 stage) are treated with cystectomy or systemic chemotherapy.…”
Section: Introductionmentioning
confidence: 99%